2018
DOI: 10.1007/s00406-018-0869-3
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drugs for patients with schizophrenia and predominant or prominent negative symptoms: a systematic review and meta-analysis

Abstract: Amisulpride is the only antipsychotic that outperformed placebo in the treatment of predominant negative symptoms, but there was a parallel reduction of depression. Cariprazine was better than risperidone in a large trial that was well-controlled for secondary negative symptoms, but the trial was sponsored by its manufacturer. Future trials should apply scientifically developed definitions such as the deficit syndrome and the persistent negative symptoms concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(118 citation statements)
references
References 61 publications
2
106
1
9
Order By: Relevance
“…78,80,81 In a metaanalysis of randomized, controlled, blinded, antipsychotic drug trials in patients with schizophrenia and either predominant or prominent negative symptoms, low-dose amisulpride, which is approved for negative symptoms in a limited number of European countries, was the only antipsychotic that was superior to placebo in the treatment of predominant negative symptoms; however, a parallel reduction of depression was also observed making it difficult to assess whether the reduction in negative symptoms was a function of improvement in depression. 82 To date, the only prospective, large-scale, randomized, double-blind evidence demonstrating the superiority of one approved antipsychotic over another in the treatment of negative symptoms comes from a rigorously designed 26week study comparing the effects of fixed-dose cariprazine 83 This study was conducted to test the hypothesis that cariprazine, as a dopamine D 3 -preferring D 3 /D 2 receptor partial agonist and serotonin 5-HT 1A receptor partial agonist, may be more beneficial than a D 2 -preferring antagonist for treating negative symptoms and cognition in patients with schizophrenia. 34,84 In this 26-week study, significant differences and clinically relevant improvement in both negative symptoms and functional impairment were demonstrated in favor of cariprazine over risperidone, suggesting a clinically meaningful treatment benefit for cariprazine in negative symptoms.…”
Section: Treatment Pharmacologic Treatmentmentioning
confidence: 99%
“…78,80,81 In a metaanalysis of randomized, controlled, blinded, antipsychotic drug trials in patients with schizophrenia and either predominant or prominent negative symptoms, low-dose amisulpride, which is approved for negative symptoms in a limited number of European countries, was the only antipsychotic that was superior to placebo in the treatment of predominant negative symptoms; however, a parallel reduction of depression was also observed making it difficult to assess whether the reduction in negative symptoms was a function of improvement in depression. 82 To date, the only prospective, large-scale, randomized, double-blind evidence demonstrating the superiority of one approved antipsychotic over another in the treatment of negative symptoms comes from a rigorously designed 26week study comparing the effects of fixed-dose cariprazine 83 This study was conducted to test the hypothesis that cariprazine, as a dopamine D 3 -preferring D 3 /D 2 receptor partial agonist and serotonin 5-HT 1A receptor partial agonist, may be more beneficial than a D 2 -preferring antagonist for treating negative symptoms and cognition in patients with schizophrenia. 34,84 In this 26-week study, significant differences and clinically relevant improvement in both negative symptoms and functional impairment were demonstrated in favor of cariprazine over risperidone, suggesting a clinically meaningful treatment benefit for cariprazine in negative symptoms.…”
Section: Treatment Pharmacologic Treatmentmentioning
confidence: 99%
“…Although various hypotheses have been developed, the etiopathogenesis of schizophrenia and EOS is not fully understood (McGuffin, 2004;Klosterkotter et al, 2011). 2 Among the rising and falling neurochemical theories, the dopamine hypothesis has remained a primary hypothesis guiding the treatment of schizophrenia.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that no drug had a beneficial effect on negative symptoms when compared to another drug (Arango et al, 2013;Millan et al, 2014;Fusar-Poli et al, 2015), meaning that head to head comparisons of different agents among each other did not result in superiority of one drug to another. The latest comparison (Krause et al, 2018) evaluated all studies that have been performed in the negative symptom population so far, and has found that amisulpride claimed superiority only to placebo, olanzapine was superior to haloperidol, but only in a small trial (n = 35), and cariprazine outperformed risperidone in a large wellcontrolled trial.…”
mentioning
confidence: 99%
“…The phenotypes of AP response identified in our study open the door to applying personalized prescription. Each cluster could benefit from differences in the efficacy and toxicity of Aps , and from other therapeutic approaches . Part of the reason for a lack of observed efficacy with several of these strategies could be that they have been applied to the wrong patients.…”
Section: Discussionmentioning
confidence: 99%